Echoes through Portuguese: teaching practices in Portuguese language curriculum development - Ferreira, Adriana (2017)
The restructured curriculum for the Timorese general secondary education (RCGSE) introduced new teaching and learning approaches, tools and materials, such as textbooks and teachers’ guides, and also the Portuguese as language of instruction. Considering the new curriculum orientations, a new model of teaching is pursued. The present study aims to analyse the teaching practice of the Portuguese language teachers concerning the use of new curricular materials, students’ evaluation and new strategies introduced by the RGSE.